EFFECTS OF VIRTUAL REALITY ON PARKINSONIAN GAIT: BLIND CONTROLLED RANDOMIZED CLINICAL TRIAL PROTOCOL - Melo, Gileno Edu Lameira de; Moura, Renata Calhes Franco de; Lopes, Jamile Benite Palma; Junior, Paulo Roberto Fonseca; Lazzari, Roberta Delasta; Duarte, Natália de Almeida Carvalho; Junior, Jose Robertto Zaffalon; Dumont, Arislander Jonathan Lopes; Kleiner, Ana Francisca Rozin; Galli, Manuela; Ferreira, Luiz Alfredo Braun; Okamoto, Erika; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Parkinson’s disease (PD) is a neurodegenerative condition that exerts a negative influence on postural control and mobility, predominantly among older adults, affecting mobility and increasing the risk of slipping, tripping and falls. Objectives: Determine the effectiveness of gait training with the aid of virtual reality on balance and gait in comparison to treadmill training and conventional gait training for subjects with PD. Methods/design: A prospective, randomized, controlled blind, clinical trial is proposed. The sample will comprise 45 individuals with Parkinson’s disease randomly allocated to three groups (Control: conventional gait training; Experimental I: treadmill training; and Experimental II: gait training involving virtual reality). Evaluations will be conducted on four occasions: 1) pre-intervention; 2) immediately after one session; 3) post-intervention; and 4) one month after last session. The evaluations will involve the Berg Balance Scale, Tinetti Test, Unified Parkinson’s Disease Rating Scale and Hoehn and Yahr Scale. The G-WALK (BTS) inertial sensor will be used for the evaluation of spatiotemporal gait variables, the Timed Up and Go test and the Six-Minute Walk Test. Training will involve 20-minute sessions held three times per week for four consecutive weeks. The results will be analyzed statistically by two-way ANOVA for the data with parametric distribution or Friedman’s two-way ANOVA for non-parametric data (α<0.05). Conclusion: The proposed study will compare gait conventional training, treadmill training and training with virtual reality with regard to improvements in gait and balance in patients with PD. The results will be published and will contribute evidence on the use of these interventions for individuals with PD.